Le révolutionnaire qui alluma la mèche : Ahmed Niyazi Bey de Resne - Faruk Bilici (Cahiers Balkaniques)
Although the elites prepared the Young Turks Revolution of 1908 and provided it strength in the big Ottoman cities, it couldn’t have been possible without the direct involvement of the army. Son of Abdullah Ağa, an Albanian notable and born in Resne (Resen), Ahmed Niyazi (1873-1913), who was the first to go underground, is a hero of this Revolution and a hero of the Greco-Turk war of 1897. He was highly praised alongside Enver Paşa who probably took umbrage at him and whose close friends murdered him.